Peningkatan Kedisiplinan Anak Usia Dini Melalui Metode Pembiasaan Token Economy - Nadar, Wahyuni (Elementeris : Jurnal Ilmiah Pendidikan Dasar Islam, 2019)
In general, the purpose of this study was to improve the discipline of early childhood through the method of token economy habituation in class II even semester 2016-2017 SD Cherry South Jakarta. The method of token economy refraction is a method of strengthening behavior by giving points (reward). In particular, the discipline referred to in this study is the presence of children on time at school. This research method is classroom action research which follows the models of Kemmis and Taggart. This study consisted of two cycles. Each cycle includes 4 stages, namely, 1) planning (planning), 2) acting (implementation), 3) observing (observation), 4) reflecting (reflection). The research time is 1 month, from April 2017 to May 2017 with the subject of research as many as 11 students, while the data is collected by observation, interviews, and documentation. The results showed that there was a significant increase in discipline in class II students. This can be evidenced by the increase in the results of quantitative calculations starting from the results of the average pre-action discipline, cycle 1 to cycle 2, namely the results of the pre-action average = 12, cycle 1 = 13.27, cycle 2 = 15 and the results of interviews concluded that the method of habituating token economy can motivate discipline in early childhood optimally. This study concludes that discipline with the method of habituating token economy can improve the discipline of early chilhood.